1997
DOI: 10.1111/j.1525-1594.1997.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Mediastinitis after Cardiovascular Surgery Using Electrolyzed Strong Acid Aqueous Solution

Abstract: Dilute povidone-iodine solution has been widely used as an irrigant for the treatment of mediastinitis. However, its use is not without adverse effects and often cause? poor prowth of pinulation tissues. To avoid the problems seen with the use of povidone-iodine solution, we applied electrolyzed strong acid aqueous solution (ESAAS) to mediastinal irrigation in 4 patients (2 infants and 2 adults) who developed mediastinitis after cardiovascular surgery. According to the "open" method, the mediastinal wound was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, ESAW has also been applied for the irrigation of body cavities 11−14 and skin ulcers. 22 From the Japan National Cardiovascular Center, Hayashi et al 11 reported four cases of postoperative mediastinitis that was successfully treated with ESAW. They reported that ESAW had no adverse effects, while a satisfactory growth of healthy granulation was also observed during convalescence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, ESAW has also been applied for the irrigation of body cavities 11−14 and skin ulcers. 22 From the Japan National Cardiovascular Center, Hayashi et al 11 reported four cases of postoperative mediastinitis that was successfully treated with ESAW. They reported that ESAW had no adverse effects, while a satisfactory growth of healthy granulation was also observed during convalescence.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 However, few applications of body cavity lavage with ESAW in clinical cases have been reported in the literature. 11 −14 In order to establish its safety and effectiveness for peritoneal irrigation in perforated peritonitis, an experimental study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…There is a possibility that NTZ may have caused cardiotoxicity, as reported by Gong et al, who observed that exposure to the drug affected the embryonic heart development of zebrafish, significantly inhibited cardiomyocyte proliferation, and promoted apoptosis, ultimately leading to cardiac tissue injury [ 63 ]. Regarding EOW, this compound has not been reported to aggravate pathological conductive presentations in the heart as part of its acute and chronic side effects [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its usefulness was further extended in Japan after several studies used ES to manage mediastinitis after cardiac operations and peritoneal abscess after abdominal operations [15,16]. The ES has been found to promote re-epithelialization, increasing the proliferation of lymphocytes and macrophages associated with collagen deposition for surgical incision healing [14].…”
Section: Discussionmentioning
confidence: 99%